A Transformation of Backward by Design Model to Designing a Curriculum - Rumanti, Elisabet Dewi (Diligentia: Journal of Theology and Christian Education, 2020)
An educational institution need a curriculum design to organize teaching and learning activities. All models of curriculum design have its own uniqueness. Since the curriculum design will be affected to all objective, teaching, learning, assessment, and express presuppositions of how the education going on that school. In this essay, therefore backward by design model is reviewed in the biblical Christian worldview context with creation, fall, redemption, and glorification approaching concept. Understanding as the main focus of backward by design model need to bring into the concept of biblical truth to see the big picture of God’s design for His creation. God’s purposeful design will affect our worldview; the way we see all aspect in life. Accordingly, the biblical Christian worldview help us to bring unit into context to give a true meaningful experiences. As the result, reconstruction of backward by design model as the transforming curriculum design to be implemented in Christian education.